Naturally functionalized silk as useful material for photonic applications. (15th March 2015) - Cavallini, Susanna; Toffanin, Stefano; Chieco, Camilla; Sagnella, Anna; Formaggio, Francesco; Pistone, Assunta; Posati, Tamara; Natali, Marco; Caprini, Marco; Benfenati, Valentina; Di Virgilio, Nicola; Ruani, Giampiero; et al.
Abstract: Silk is a natural fibre obtained from the Bombyx mori silkworm cocoons that can be used in a wide range of fields thanks to its inherent multifunctionality. Post-production steps are necessary to impart colour to the fibres to employ the material for optics and photonic applications, such as in fluorescence-based optofluidic devices in lab-on-a-chip realization. Here we present an intrinsically greener dyeing approach for fabricating naturally functionalized silk, where highly-fluorescent organic dyes with lasing properties are in vivo up-taken by silkworms once introduced in the artificial diet. A detailed photoluminescence spectroscopy investigation is implemented to test whether the dyes are effectively incorporated within the silk proteins, in correlation with the silkworm gland positions where proteins extraction is held. Light amplification characteristics are demonstrated in silk extracted from glands of silkworm fed with artificial diet doped with Rhodamine B dye.